A Study on the Effects of Pregabalin and Amitriptyline in Treatment of Patients with Painful Diabetic Neuropathy - Unaiza Sharif, Awais Shabbir, Faramarz Khan, Farhat Ul Ain, Muhammad Khurram, Abdul Kabeer Baig (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To compare the effect of Amitriptyline and Pregabalin in treatment of painful diabetic neuropathy. Material and Methods: The design of this study was Randomized Controlled Trial study design. This study was conducted in the Department of Medicine in, Holy Family Hospital, Rawalpindi and the duration of this study was Six months after the approval of synopsis i.e from 1st November 2019 to 1st May 2020. Approval from ethical committee of the hospital was taken. Written informed consent was taken from patients. Consent form is attached with this. Patients were randomly allocated into two groups by lottery method. The dose of Pregabalin was used as 50mg thrice daily for a period of six weeks and label as group-A and group B received amitriptyline as 25mg once daily before bedtime for a period of six weeks as prescribed by a senior consultant who was blind to object of the study. At the start and end of treatment pain was marked by patients on Visual Analogue Scale (VAS) and numerical score. It was noted on the Performa. Results: Total 100 patients were included according to the inclusion criteria of the study. The dose of Pregabalin was given in patients in group-A and group-B received amitriptyline. Mean age (years) in the study was 55.87+6.43 whereas there were 55 (55.0) male and 45 (45.0) female patients who were included in the study according to the inclusion criteria. In our study, frequency and percentage of effect (pain relief) among Pregabalin and Amitriptyline in treatment of painful diabetic neuropathy was 27 (54.0) and 11 (22.0) respectively which was statistically significant (p-value 0.001). Practical Implication: In this study Pregabalin is more responsible for pain relief than Amitriptyline in treatment of painful diabetic neuropathy. Further studies at multiple studies must be conduct in future for determining the efficacy of amitriptyline and Pregabalin in diabetic neuropathy in order to formulate guidelines for management of diabetic peripheral neuropathy. Conclusion: The study concluded that Pregabalin is more responsible for pain relief than Amitriptyline in treatment of painful diabetic neuropathy. Further studies at multiple studies must be conduct in future for determining the efficacy of Pregabalin and amitriptyline in diabetic neuropathy in order to formulate guidelines for management of diabetic peripheral neuropathy. Keywords: Amitriptyline, Pregabalin, Neuropathy, Pain Relief, Diabetic Sensorimotor Polyneuropathy, Prevalence.